The Influence of Parental Roles on Adolescents' Knowledge of Puberty at MTS BI Islami - Rahmawati, Rahmawati; Basri, Zaenal; Nurleliana, Nurleliana; Ibrahim, Aliya Az Zahra (Miracle Journal of Public Health, 2025)
Adolescents' lack of knowledge about puberty greatly affects the behavior of young people. Adolescents who lack information can trigger bad behavior; curiosity is more dominant, so it results in fatal things if not balanced with assistance from parents. The Role of Parents as the Main and Trusted Source The purpose of the study was to determine the role of parents in adolescent knowledge about puberty in class VIII students at MTS BI Islami. The type of research is quantitative with a cross-sectional study design. The population in this study were all VIII grade students, totaling 34 students, with a sample size used in this study of 31 students, while sampling techniques by means of simple random sampling. The instrument used in data collection is a questionnaire. To test the hypothesis, the data analyst used inferential statistics: simple linear regression. The results showed that the role of parents of students in the category of sufficient by 3%, good at 39%, and very good at 58%, while the knowledge of adolescents about puberty was in the medium category at 42% and high by 58% with high knowledge. The conclusion from the results of the data analysis showed. ????????????= 0.030 means , which means there is a significant influence of the role of parents on adolescents' knowledge about puberty.